Possuir ou experienciar? : entendendo as relações entre o materialismo e o experiencialismo ao longo do processo de consumo de uma experiência - Machado, Maria Amália Dutra (2018)
Some studies are named experience recommendation and have suggested that experience purchase provides more welfare and happiness to consumers because gives life events for the individual. However, recent evidence argues that some consumers acquire an experience with the intention to obtaining tangible artifacts that are held in their possession. Therefore, the present work objective is comprehending which relationships exist between the dimensions of materialist and experientialist behaviors throughout the process of consumption of an experience. In this way, this exploratory qualitative investigation begins with a literature review to propose four dimensions of the materialist and experientialist consumption behavior. Then, 13 consumers are interviewed before and after they realized an international travel. Also, photographys and videos of the moments lived throughout the trip made by the own participants are analyzed. The results point the definition of materialist consumption behavior as the action of using a product with the intention of obtaining an artifact that is held in individual possess, and experientialist consumption behavior as the action of using a product with intention of obtaining events unusual in the life’s subject. Data shows that same consumer can present aspects of both behavior throughout consumption process. This study contributes in three ways to the experience recommendation theory. First, the analysis shows definitions of the actions and intentions of consumer and aspects related to materialism and experientialism. Second, the results support the proposed categorization of the products, that can be material goods and other artifacts; services provided throughout the consumption; or experiences, that are unusual activities realized by the consumer throughout process. Third, the analysis demonstrates consumption process is a set of individual action along a determined period.